Lethal licorice [large type] - Flower, Amanda (Flower, Amanda. Amish candy shop mystery., 2018)
"Caring for her recently widowed grandmother, Bailey King plans to honor her grandfather's memory by entering the annual Amish Confectionery Competition in Harvest, Ohio. When a candy maker from a neighboring town who wanted Englischer Bailey disqualified for being an outsider dies from an allergy to an essential licorice ingredient, Bailey becomes a suspect"--